Taking the sting out of assessment: The experiences of trainee teachers experimenting with innovative alternative performance assessment in the History classroom (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
This article explores the experiences of History and Social Sciences (History) trainee teachers (n=33) and their learners during the implementation of five versatile and innovative alternative performance assessment strategies in their diverse classroom settings during their practicum at schools. Originally designed for the corporate staff training environment, and subsequently utilised as community building and data collection techniques in a participative community-engaged research project, these five interactive activities were adapted to act as innovative teaching and alternative formative performance assessment strategies in the History classroom, the latter of which is the main focus of this article. The article is anchored in a social constructivist and dialogic theoretical framework and argues that alternative performance assessment techniques that are non-graded, interactive, formative and dialogic in nature, take place within an atmosphere of emotional safety, and integrate a strong element of enjoyment, are able to remove the anxiety that often characterises both summative and graded formative assessment. This, in turn, makes learners more receptive to learning and brings History to life in the classroom. In an attempt to answer two interrelated research questions: “how did trainee History teachers experience the implementation of innovative alternative performance assessment strategies”, and “how did they perceive the response of the learners to a fresh approach to formative assessment”, the article employs a qualitative research methodology which rests on research findings generated through the use of data gathered from written, visual and oral feedback from the participants during and after a practical workshop which prepared them for the implementation phase of the study. The research findings suggest, inter alia, that both the trainee teachers and their learners enjoyed a fresh, non-threatening approach to formative assessment and that the learners participated freely and enthusiastically in groups when implementing these formative assessment strategies. The findings also indicate some challenges including time management, classroom management, and appropriate facilitation skills in managing more advanced learners who, it was found, tended to overpower less confident learners in their groups. It finally offers recommendations for improvement should History teachers prefer to implement these alternative performance assessment strategies in their classrooms.The findings also indicate some challenges including time management, classroom management, and appropriate facilitation skills in managing more advanced learners who, it was found, tended to overpower less confident learners in their groups. It finally offers recommendations for improvement should History teachers prefer to implement these alternative performance assessment strategies in their classrooms.
Keywords: Alternative formative assessment; Assessment strategies; History education; Trainee teachers; History learners